2015 International Conference on Renewable Energy Research and Applications (ICRERA) 2015
DOI: 10.1109/icrera.2015.7418659
|View full text |Cite
|
Sign up to set email alerts
|

Building DC microgrids: Planning of an experimental platform with power hardware in the loop features

Abstract: DC power distribution systems for building application are gaining interest both in academic and industrial world, due to potential benefits in terms of energy efficiency and capital savings. These benefits are more evident were the end-use loads are natively DC (e.g., computers, solid-state lighting or variable speed drives for electric motors), like in data centers and commercial buildings, but also in houses. When considering the presence of onsite renewable generation, e.g. PV or micro-wind generators, sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The reliability cost is dependent on the reliability index during the planning horizon. The planning model of experimental DC microgrids in University of Naples Feerico II is presented in [35]. The microgrids consist of several generation mixes such as PV, wind, fuel cell, supercapacitor, and battery energy storages, DC loads, smart loads, and electric vehicle (EV) chargers.…”
Section: DC Microgrids Planningmentioning
confidence: 99%
“…The reliability cost is dependent on the reliability index during the planning horizon. The planning model of experimental DC microgrids in University of Naples Feerico II is presented in [35]. The microgrids consist of several generation mixes such as PV, wind, fuel cell, supercapacitor, and battery energy storages, DC loads, smart loads, and electric vehicle (EV) chargers.…”
Section: DC Microgrids Planningmentioning
confidence: 99%
“…Information and Communication Technology (ICT) devices, including computers, monitors, networking equipment, and battery chargers, mostly use direct current (DC) and require a power supply module. Recently, field research and trials have been conducted with buildings offering DC power sockets, removing the need for SMPSs 27 , 28 . Recent studies found that SMPSs can have a significant effect on EEM accuracy and can cause deviations of up to 582% when comparing smart meters to conventional meters 29 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Current research and development efforts in DC power systems for buildings are international [8,[10][11][12][13][14][15]. In Japan and South Korea, partnerships between government, academic, and industrial groups have made these two nations leaders in the technological development of DC-powered buildings and microgrids [8].…”
Section: Introductionmentioning
confidence: 99%